2015
DOI: 10.1007/s00414-015-1250-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of 75 SNPs using arrays for individual identification in five population groups

Abstract: Single nucleotide polymorphism (SNP) typing offers promise to forensic genetics. Various strategies and panels for analyzing SNP markers for individual identification have been published. However, the best panels with fewer identity SNPs for all major population groups are still under discussion. This study aimed to find more autosomal SNPs with high heterozygosity for individual identification among Asian populations. Ninety-six autosomal SNPs of 502 DNA samples from unrelated individuals of five population g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…2b ). We removed the least heterozygous SNP of any two SNPs, with LD and close genetic distance based on criteria of Kidd et al [ 21 ] and Hwa et al [ 23 ]. In addition, SNPs located in the HLA region were removed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2b ). We removed the least heterozygous SNP of any two SNPs, with LD and close genetic distance based on criteria of Kidd et al [ 21 ] and Hwa et al [ 23 ]. In addition, SNPs located in the HLA region were removed.…”
Section: Resultsmentioning
confidence: 99%
“…There is no overlap between Dutch selected IISNPs and the established IISNP panels [ 13 , 20 , 23 , 35 ]. One of our selected SNPs (rs1866141) is located in an intronic region of the highly expressed GNLY gene (MIM # 188855).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These STR regions are amplified using the DNA samples from biological evidence, such as semen, blood, sperm, or skin cells, and analyzed for individual identification. 3–6…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a universal panel of 92 SNPs was developed for individual identification[ 9 ]. Another panel used 75 SNPs for Eastern Asian populations[ 10 ]. A recent simulation study showed that only 60 optimized SNPS are required to differentiate individuals in the global population[ 7 ].…”
Section: Introductionmentioning
confidence: 99%